Urgency of Falsum in Indonesian Criminal Justice System as Basis for Revision; An Islamic Perspective - Mia Amiati; Taufik Rachman; R.B. Muhammad Zainal Abidin (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2024)
In Indonesian Islamic law,